Analisis Hasil Pencacahan Sampah Rumah Tangga Menggunakan Mesin Depackaging Waste Tipe Hammer Mill Melalui Simulasi CFD-DEM - Hafidh Ihwanul Isro; Arif Rahman Saleh; Nurmala Dyah Fajarningrum (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
separating and shredding organic and inorganic waste. This study aims to analyze the process of shredding household waste using the Computational Fluid Dynamics–Discrete Element Method (CFD-DEM) and determine the optimal operational parameters based on variations in rotor speed. The research method uses numerical simulation with SolidWorks 2024 software for geometric modeling and Ansys Rocky 2023 R1 for CFD-DEM simulation. The rotor speed variations used are 1000 RPM, 2500 RPM, and 4000 RPM with a mass flow rate of 4 tons/hour and a simulation duration of 2 seconds. The parameters analyzed included particle mass flow rate, shredding characteristics, and power consumption. The simulation results showed that a speed of 1000 RPM produced the most optimal performance with a maximum capacity of ±4 tons/hour and a stable shredding response compared to other variations. At 2500 RPM, there were high fluctuations with low capacity (±0.6 tons/hour), while at 4000 RPM, the capacity was moderate (±1.1 tons/hour) but still did not exceed the performance of 1000 RPM. Based on these results, it can be concluded that a rotor speed parameter of 1000 RPM is the most effective condition for improving the grinding efficiency and production capacity of a hammer mill-type Depackaging machine based on CFD-DEM simulation.